Impact of papanicolaou smear upon physical and psychosocial aspects of women's health - mohammed, Isra'a; Baha'aedeen, Ezedeen (Iraqi National Journal of Nursing Specialties, 2012)
Objectives: To identify the impact of Pap smear upon physical and psychological and social aspects of women'shealth.Methodology: A purposive sample of (71) women. The data were collected through the utilization of thedeveloped questionnaire which consists of four major parts: 1. demographic 2.Physical domain 3. Psychologicaldomain 4. social domain and by means of interview technique with the women who were individually interviewedin the Baghdad Teaching Hospital/ the Consultant Clinic, Teaching Laboratories/ Medical City, AL-ElwyiahMaternity Hospital . The data collection process has been performed from April 17th, 2011 until the August 10th,2011. Descriptive and inferential statistical analysis procedures were employed for the data analysis.Results: Most of women feel pain during the Pap smear procedure, Women commonly feel stressed, discomfortand anxious from conducting Pap smear, most women did not have enough time to conduct the Pap smear andbusy with rather things. There is fear from conducting pap smear it is fear from a positive result, There are papsmear influence on marital relationshipRecommendations: The study recommends that an intensive comprehensive, obligatory educationalprograms(campaigns) are needed to improve awareness of the women about pap smear test and stress theimportance of regular smears as a preventative measure, Reducing fears and anxieties associated with a Papsmear that can be alleviated with better information sharing about Pap smear procedure. Give each womanwritten information on Pap smears; explain the purpose of the Pap smear, the instruments to be used, theprocedure, possible test results and follow up and the recommended frequency of Pap smears